(untitled) (Journal of Informatics and Mathematical Sciences, 2009)
A pair of mixed type multiobjective second-order symmetric dual program is formulated. Weak, strong and converse duality theorems are validated under bonvexity-boncavity and pseudobonvexity-pseudoboncavity of the Kernel function appearing in the primal and dual programs. Under additional conditions on the Kernel functional constituting the objective and constraint functions, these programs are shown to be self dual. This formulation of the programs not only generalizes mixed type first order symmetric multiobjective duality results but also unifies the pair of Wolfe and Mond-Weir type second order symmetric multiobjective programs.